Ice-sounding airborne synthetic aperture radar depth profiles from Recovery Ice Stream 2016/17 and Rutford Ice Stream 2019/20 to test the RGB-Doppler-Decomposition method. ... - Arenas Pingarron, Alvaro; Brisbourne, Alex; Corr, Hugh; Jordan, Tom; Robinson, Carl; Martin, Carlos; Nicholls, Keith; Smith, Andrew (NERC EDS UK Polar Data Centre, 2023)
This data set corresponds to data acquired by the British Antarctic Survey (BAS) airborne Synthetic Aperture Radar (SAR) PASIN2 (Polarimetric Airborne Scientific INstrument, mark 2), designed for deep ice sounding and basal 3d-mapping. The data set includes the processed SAR images as depth profiles in the Recovery Ice Stream and Rutford Ice Stream, respectively downstream and upstream of the grounding line, and respectively for the 2016/17 FISS (Filchner Ice Shelf System) and the 2019/20 BEAMISH (Bed Access, Monitoring and Ice Sheet History) projects, both during the Antarctic Summer. With multiple antennas for transmission and reception at 150-MHz central frequency, and an across-track physical array, PASIN2 resolves the ambiguities for distinguishing between scatterers from port and starboard directions; however, in the two SAR images of the current dataset the port/starboard ambiguities are not resolved. On this dataset the user will be able to apply the RGB Doppler Decomposition method in the Doppler ... : The raw data was collected by the airborne Synthetic Aperture Radar (SAR) PASIN2. It is 150-MHz coherent pulsed radar, transmitting chirped pulses with linear frequency sweep, with 13 MHz bandwidth and effective pulse repetition frequency 125 Hz. On board of a De Havilland DHC-6 Twin Otter aircraft ("VP-FBL), in ice-sounding flights the nominal speed is 60 m/s, and the terrain clearance (height above closest surface) is 300 m. PASIN2 has 12 antenna elements: 8 underwing folded-dipoles switching between transmit (TX) and receive (RX) modes, and 4 printed-dipoles being RX-only attached to the fuselage belly. The data processing is performed off-line, with a full workflow consisting of: 1) channel calibration; 2) 2D SAR imaging, based on pulse-compression for range dimension, and back-projection for along-track dimension; 3) Direction of Arrival estimation (DoA) of the remaining across-track angle, based on the non-linear MUSIC algorithm, by using several SAR images from different transmitters or receivers; and ...